Islamic Legal Perspective on the Implementation of Online Marriage Contracts during the Covid-19 Pandemic - Sujono, Imam; Mangesti, Yovita Arie; Suhartono, Slamet; Kamaruddin, Zaleha (Universitas Islam Sultan Agung, 2022)
The validity of a marriage is the fulfillment of the pillars and conditions of marriage as stipulated in Islamic law. One of the pillars currently being discussed is the online Ijab and Qabul (marriage contract), considering the COVID-19 pandemic, there has been much news about online marriage ceremonies due to various constraints. Moreover, technology is becoming increasingly advanced and evolving, making human tasks easier. The aim of this study is to examine the legality of online marriage contracts that occurred during the COVID-19 pandemic. This research uses a qualitative research method with a library research type, referencing journals, articles, and books related to the main theme of online marriage contracts. All references, including legal and non-legal sources, are presented and then analyzed carefully. Scholars and fiqh experts have provided arguments about the validity of marriage through online contracts. According to the scholars, an online marriage contract is valid if what is meant by one assembly is one time, not one place. Thus, after the Ijab is stated, the Qabul must also be stated immediately. The research results show that marriage contracts conducted online during the COVID-19 pandemic are legally valid, thereby contributing to resolving the difficulties faced by prospective brides and grooms in gathering to conduct the marriage contract due to social restrictions. The validity of online marriage contracts represents a legal renewal that previously considered that marriage contracts must be conducted in one place.